2017
DOI: 10.1007/s10126-017-9785-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Inhibitory Compounds Against Singapore Grouper Iridovirus Infection by Cell Viability-Based Screening Assay and Droplet Digital PCR

Abstract: Singapore grouper iridovirus (SGIV) is one of the major causative agents of fish diseases and has caused significant economic losses in the aquaculture industry. There is currently no commercial vaccine or effective antiviral treatment against SGIV infection. Annually, an increasing number of small molecule compounds from various sources have been produced, and many are proved to be potential inhibitors against viruses. Here, a high-throughput in vitro cell viability-based screening assay was developed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…Previous studies demonstrated that HT and HHT inhibit replication of CHIKV, VZV [19], and the Sindbis virus (SINV) [28]. HHT has further been shown to exert antiviral effects against coronavirus (CoV) [20] and HBV [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that HT and HHT inhibit replication of CHIKV, VZV [19], and the Sindbis virus (SINV) [28]. HHT has further been shown to exert antiviral effects against coronavirus (CoV) [20] and HBV [16].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing research on lipids in aquaculture had been illuminating. 2-HOM has been characterized as an inhibitor of SGIV that benefits from its interfering with SGIV-ORF088L myristoylation, and resistance against SGIV entry and replication (76). Exploiting specific lipid requirements of pathogens, and delineating the intricate interactions of these pathogens with cellular lipids and the modification of their metabolism, might provide new approaches for antiviral therapies (50).…”
Section: Discussionmentioning
confidence: 99%
“…For now, fish cell lines have been established from a variety of different fish species and tissues, which collectively are referred to as the fish invitrome (Bols, Pham, Dayeh, & Lee, ). The fish invitrome is widely used in developing antiviral strategies and comprehending the interaction between virus and the cells of hosts (Jia et al, ; Le et al, ; Zhang et al, ) and non‐hosts (Pham, Lai, Lee, Bols, & Chiou, ). Kim and colleagues reported that VHSV was detected in wild silver pomfret in Korea, indicating silver pomfret was the natural host of VHSV (Kim, Choi, Kim, & Oh, ).…”
Section: Introductionmentioning
confidence: 99%